Investigating Waqf Property Resources of Institutional Mutawalli in Malaysia - Abd Mutalib, Hasyeilla; Maamor, Selamah (UUM Press, 2018)
The purpose of this study is to investigate the waqf property resources of institutional mutawalli in Malaysia. This study employs qualitative method by investigating four selected institutional mutawalli in Malaysia in terms of their property resources. The institutional mutawalli were selected by using purposive sampling method. Formal and semi-structured interviews were carried out with the waqf manager, deputy CEO, waqf coordinator and manager of waqf development unit as representatives of the institutional mutawalli. In this study, waqf property resources of the institutional mutawalli are categorized into three elements which are i) the type and number of physical waqf property, ii) the total value of waqf property including cash waqf, and iii) the categories of waqf property. These elements provide some general insights into the waqf property resources of each institutional mutawalli. Thus, from the information, each institutional mutawalli can take proactive action to ensure that all waqf properties in their institution are well managed, as well as being administered and developed accordingly as it can contribute to the socio-economic advancement of the Ummah.